Sustainable Tourism Development in Tanzania - Anderson, Wineaster; Mossberg, Lena.; Andersson, Tommy D. (Newcastle-upon-Tyne : Cambridge Scholars Publisher, 2021)
Tanzania is rivalled by few countries, if any, in terms of its bountiful natural and cultural tourist attractions. Given that tourism development, if sustainable, is an outstanding policy for distributing welfare, even to less developed parts of a country, this field is of particular importance to Tanzania. In this edited volume, prominent scholars focus on the practises and policies of tourism development, with a particular eye on the case of Tanzania. They explore the demand for sustainability from international tourists, the need for local food and linkages between the tourism and agricultu.
Intro -- Table of Contents -- Preface -- Chapter One -- Theme 1 -- Chapter Two -- Chapter Three -- Chapter Four -- Theme 2 -- Chapter Five -- Chapter Six -- Chapter Seven -- Theme 3 -- Chapter Eight -- Chapter Nine -- Chapter Ten -- Theme 4 -- Chapter Eleven -- Chapter Twelve -- Chapter Thirteen -- Contributors -- Sustainable Tourism Development in Tanzania -- Edited by Wineaster Anderson, Lena Mossberg and Tommy D. Andersson
Description based upon print version of record.
Master record variable field(s) change: 050, 082, 650
Keywords: Ecotourism -- Tanzania; Tourism -- Environmental aspects -- Tanzania; Sustainable development; Electronic books; Electronic books